Analisis Pengaruh Kualitas Website Berhadap kepuasan Pengguna Berdasarkan Metode Webqual 4 - Lukman Arie Setio Budi; Sulistiowati Sulistiowati; Sri Suhandiah (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Based on the problems that occur for example at SMAN 2 CITY MOJOKERTO, where many cases of both the part of teachers, students and outsiders who struggle to get vital information from SMAN 2 CITY MOJOKERTO. Because of this, they invented www.sman2mojokerto.com website, where students as consumers can get the information that is accessible online anytime and anywhere. Then made a website as a means of delivering information that can be accessed anytime and anywhere. But the website has been built yet meet the needs of visitors. Based on data collection on the number of total required number of visits, the website is not in accordance with the amount included in the visit. In this case the user factors play an important role over the use and utilization of information technology. To determine the level of success of a technology implementation, the extent to which users can accept and understand that technology is an important thing to be able to assess the success of the implementation. Therefore, it is necessary to evaluate the www.sman2mojokerto.com website to find out the cause of the lack of interest of Internet users to the website www.sman2mojokerto.com the user satisfaction, the writer used WebQual 4.0 to test it.